2013
DOI: 10.1080/01463373.2013.776988
|View full text |Cite
|
Sign up to set email alerts
|

Consuming Image: How Mass Media Impact the Identity of People with Disabilities

Abstract: This research investigated what people with disabilities think about media representations of their community and how mass media impact their disability identity. The study found that respondents (N ¼ 359) think American media portray people with disabilities both negatively and positively. Perceived positive media representation of people with disabilities led to affirmation of their disability identity even when the media messages were perceived as unrealistic, whereas negative media representation led to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 26 publications
1
58
0
9
Order By: Relevance
“…Research examining news media framing of people with disabilities has long revealed problematic media representations (Zhang & Haller, 2013), such as the use of images and words that are stereotypical (Haller, 2000;Haller, 2010;O'Malley, 2009). Zhang and Haller (2013) found that media portrayals such as the victim frame negatively impact the perceived self-identity of people with disabilities.…”
Section: Framing Of People With Disabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research examining news media framing of people with disabilities has long revealed problematic media representations (Zhang & Haller, 2013), such as the use of images and words that are stereotypical (Haller, 2000;Haller, 2010;O'Malley, 2009). Zhang and Haller (2013) found that media portrayals such as the victim frame negatively impact the perceived self-identity of people with disabilities.…”
Section: Framing Of People With Disabilitiesmentioning
confidence: 99%
“…Zhang and Haller (2013) found that media portrayals such as the victim frame negatively impact the perceived self-identity of people with disabilities.…”
Section: Framing Of People With Disabilitiesmentioning
confidence: 99%
“…The notion that images of and narratives about disability can influence people's thinking is widely accepted (Moody 2008;Harnett 2000;Wohl 2017;Zhang and Haller 2013;Black and Pretes 2007;Van Kraayenoord 2011), but that influence is interpreted in a variety of ways.…”
Section: Influencementioning
confidence: 99%
“…Among the most persistent is the association of disability with malevolence. Deformity of body symbolizes 1 Zhang and Haller (2013) argue, in an article discussed below, that stories about disability in news media not only provide frameworks for able-bodied people in their understanding of disability, but shape the self-understanding of people with disabilities as well. 2 See one very recent example of the first trope, the character Dr. Maru (also known as Dr.…”
Section: Introductionmentioning
confidence: 99%
“…When media portrays people with disabilities as "sickly and helpless victims", it implies that a "disabled person's life is inferior to […] an able-bodied person's life" (Zhang & Haller, 2013). In addition, physical and mental disabilities have been negatively affected by portrayals of insane or murderous characters in media.…”
Section: How We Learn: the Problem With Stereotypesmentioning
confidence: 99%